2021
DOI: 10.3390/en14185698
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Conjugate Heat Transfer in Ribbed Channel on Thermal Conductivity of Channel Wall: An LES Study

Abstract: A series of large eddy simulations was conducted to analyze conjugate heat transfer characteristics in a ribbed channel. The cross section of the rib is square and the blockage ratio is 0.1. The pitch between the ribs is 10 times the rib height. The Reynolds number of the channel is 30,000. In the simulations, the effect of the thermal resistance of the solid wall of the channel on convective heat transfer was observed in the turbulent flow regime. The numerical method used was based on the immersed boundary m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…These are examples of the pitch and shape of the rib, the angle of attack of the rib, the coefficient of channel blockage, etc. [7][8][9][10]. Recently, Mousavi et al [25] described a variety of passive methods used to intensify the heat transfer process.…”
Section: Review Of New Advancesmentioning
confidence: 99%
See 1 more Smart Citation
“…These are examples of the pitch and shape of the rib, the angle of attack of the rib, the coefficient of channel blockage, etc. [7][8][9][10]. Recently, Mousavi et al [25] described a variety of passive methods used to intensify the heat transfer process.…”
Section: Review Of New Advancesmentioning
confidence: 99%
“…Considering the intensification of heat exchange, we recognise passive or active methods. Passive methods, such as increasing the area of heat transfer or inserting solid particles into a fluid, or increasing the intensity of turbulence by shaping an insert with a dedicated perforation or mechanically deformed pipe, have been studied for several years, and some of them have become commercial solutions [7][8][9][10]. Active methods, such as air injection, bubble or vortex generation, or proper pulsation, can lead to an increase in the heat transfer coefficient and, finally, can produce an increase in heat exchange [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the pitch and shape of the rib, the angle of attack of the rib, and the coefficient of channel blockage have a significant effect on heat transfer [14]. Joon Ahn et al [15] made the LES simulation of the dependence of conjugate heat transfer in a ribbed channel on the thermal conductivity of the channel wall. The authors noted that for such a case, RANS underpredicts heat transfer and does not accurately predict local peaks, while the same predictions using LES give more accurate results.…”
Section: Review Of Contribution To the Special Issuementioning
confidence: 99%
“…The authors concluded that if the conductivity ratio between the solid wall and the fluid exceeded 100, the heat transfer characteristics were similar to those under isothermal conditions, and the vortices at the corners of the ribs strongly influenced the convective heat transfer. For a conductivity ratio below 100, vortices located in the corners played an important role in heat transfer [15]. The authors concluded that the 'thermal resistance of the solid wall of the channel to convective heat transfer was observed in the turbulent flow regime' [15].…”
Section: Review Of Contribution To the Special Issuementioning
confidence: 99%
See 1 more Smart Citation